PERTIMBANGAN HUKUM HAKIM DALAM MENERAPKAN PASAL 2 UU TIPIKOR (STUDI PUTUSAN NOMOR77/PID.SUS-TPK/2018/PN.KDI) - Aulia Putri Khairunnisa; Itok Dwi Kurniawan (Verstek, 2023)
This research examines the problem, what are the legal considerations of judges in applying Article 2 of the Corruption Crime Law to Decision Number 77/Pid.Sus-TPK/2018/PN.Kdi. The research method in writing this journal is normative legal research. This method involves an analysis of legal materials in the form of applicable legal regulations and existing legal documents. The legal material in this study is Law Number 20 of 2001 concerning Corruption Crimes which is focused on Article 2. The results of the research show that as a judge has a great responsibility in making decisions that are fair and based on the law. Some of the legal considerations that must be considered by the judge in making a decision include applicable law, existing facts and evidence, principles of justice, public policy considerations, appropriate punishment, and the interests of the victim. Keywords: Corruption Crime, Judge's Legal Considerations; Article 2 of the Corruption Law